Aberrant expression of MYD88 via RNA‐controlling CNOT4 and EXOSC3 in colonic mucosa impacts generation of colonic cancer. Issue 12 (25th October 2021) - Tsuda, Masumi; Noguchi, Misa; Kurai, Tsuyoshi; Ichihashi, Yuji; Ise, Koki; Wang, Lei; Ishida, Yusuke; Tanino, Mishie; Hirano, Satoshi; Asaka, Masahiro; Tanaka, Shinya
Abstract: In 2020, the worldwide incidence and mortality of colorectal cancer (CRC) were third and second, respectively. As the 5‐y survival rate is low when CRC is diagnosed at an advanced stage, a reliable method to predict CRC susceptibility is important for preventing the onset and development and improving the prognosis of CRC. Therefore, we focused on the normal colonic mucosa to investigate changes in gene expression that may induce subsequent genetic alterations that induce malignant transformation. Comprehensive gene expression profiling in the normal mucosa adjacent to colon cancer (CC) compared with tissue from non‐colon cancer patients was performed. PCR arrays and qRT‐PCR revealed that the expression of 5 genes involved in the immune response, including MYD88, was increased in the normal mucosa of CC patients. The expression levels of MYD88 were strikingly increased in precancerous normal mucosa specimens, which harbored no somatic mutations, as shown by immunohistochemistry. Microarray analysis identified 2 novel RNA‐controlling molecules, EXOSC3 and CNOT4, that were significantly upregulated in the normal mucosa of CC patients and were clearly visualized in the nuclei. Forced expression of EXOSC3 and CNOT4 in human colonic epithelial cells increased the expression of IFNGR1, MYD88, NFκBIA, and STAT3 and activated ERK1/2 and JNK in 293T cells. Taken together, these results suggested that, in the inflamed mucosa, EXOSC3‐ and CNOT4‐mediated RNA stabilization, including that of MYD88, may trigger the development of cancer and can serve as a potential predictive marker and innovative treatment to control cancer development. Abstract : RNA‐controlling CNOT4 was significantly expressed in normal mucosae adjacent to colon cancers. IHC for CNOT4 was performed in 17 CCs and 15 NCCs, and representative images in paracancerous normal colonic mucosae, the paired tumor lesions in CCs, and normal mucosae in NCCs were displayed.